Stratedi Pemerintah Desa dalam Meningkatkan Kesadaran Masyarakat dalam Membayar Pajak Bumi dan Bangunan - Nugroho, Miko; Kusdarini, Eny (Universitas Negeri Malang, 2019)
This paper aims to reveal the strategy of the Government of Kliwonan Village, Banyuurip District, Purworejo Regency to increase public awareness in paying for land and building taxes. This study uses a qualitative approach with a descriptive research type. Purposive sampling used to determine the informant. Observation, interviews, and documentation used for collecting data. This study shows the strategy undertaken by the government is collaborating with the Banyuurip District Government, optimizing all village officials, mobilizing PKK and Dasa Wisma Mobilization Teams, conducting socialization, and visiting taxpayers directly.